2022
DOI: 10.1088/1361-6668/ac4ff1
|View full text |Cite
|
Sign up to set email alerts
|

High-performance Ba1−x K x Fe2As2 superconducting joints for persistent current operation

Abstract: High-performance superconducting joint is the key to achieving persistent-mode magnet. Herein, the superconducting joint between Ba1-xKxFe2As2 (Ba-122) superconducting tapes was prepared by a simple cold-pressing method, and the joint resistance of the iron-based superconducting joint was estimated by field-decay method for the first time. Via the SEM, EBSD, EPMA and XCT measurement, it is found that the joint sample CP80 shows fine performance. At 4.2 K and 10 T, a transport critical current Ic of 105 A for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…For further enhancement of the J c in round wires, which are more suitable for winding coils, an improvement in texturing, an increase in the density of the superconducting core, and a reduction in impurities are demanded. On the other hand, other aspects of tape and/or wire developments besides enhancement of the J c have been studied, such as multi-filament wire fabrication [32][33][34], fabrication of coils using long wires or tapes [29,31,[35][36][37][38][39], making joints between tapes [40][41][42], evaluation of the strain effect on the J c [7,43], and low cost fabrication using a Cu or Cu/Ag composite metal sheath [44][45][46]. In particular, fabrication of multi-filament wires and tapes is an indispensable process toward applications, to provide protection against magnetic flux jumps and thermal quenching [47], and to reduce the alternating current (AC) loss induced by the eddy currents in the metallic matrix and the inter-filament coupling currents [2].…”
Section: Introductionmentioning
confidence: 99%
“…For further enhancement of the J c in round wires, which are more suitable for winding coils, an improvement in texturing, an increase in the density of the superconducting core, and a reduction in impurities are demanded. On the other hand, other aspects of tape and/or wire developments besides enhancement of the J c have been studied, such as multi-filament wire fabrication [32][33][34], fabrication of coils using long wires or tapes [29,31,[35][36][37][38][39], making joints between tapes [40][41][42], evaluation of the strain effect on the J c [7,43], and low cost fabrication using a Cu or Cu/Ag composite metal sheath [44][45][46]. In particular, fabrication of multi-filament wires and tapes is an indispensable process toward applications, to provide protection against magnetic flux jumps and thermal quenching [47], and to reduce the alternating current (AC) loss induced by the eddy currents in the metallic matrix and the inter-filament coupling currents [2].…”
Section: Introductionmentioning
confidence: 99%
“…The recent work of Zhu et al [22], reports an effective method for the joining of IBS superconducting tapes based on the cold pressing technique. The authors have shown that a high-performance, ultra-low-resistance joint can be formed by cold pressing, and that higher pressures generally improve the quality of the joint.…”
mentioning
confidence: 99%